Ibn Thufail and His Contributions in the Field of Islamic Philosophy: Thoughts and Developments - Latif, Mukhlis (Jurnal Adabiyah, 2023)
Islamic philosophical thought is actually a study that discusses the essence and substance of the thinker. As an Islamic thinker, of course, various Islamic philosophical thoughts are related to Islamic teachings. This can be understood because Islam seems to be a "spring" in the middle of a dry desert. This study aims to explore the thoughts of Ibn Thufail in the context of Islamic philosophy. This research is a literature review by prioritizing qualitative-descriptive research that tries to analyze thoughts based on books or other research works that substantively discuss the thoughts of an Islamic thinker, namely Ibn Thufail. The results of the study confirm that the context of Ibn Thufail's thought in the field of Islamic philosophy is influenced by the reality of the times when Ibn Thufail lived, namely the massive development of science. الملخص الفكر الفلسفي الإسلامي هو في الواقع دراسة تناقش طبيعة وجوهر المفكرين. كمفكر إسلامي ، بالطبع ، ترتبط العديد من الأفكار الفلسفية الإسلامية بالتعاليم الإسلامية. هذا أمر مفهوم لأن الإسلام يبدو أنه "عين ماء" في وسط صحراء جافة. تهدف هذه الدراسة إلى استكشاف أفكار ابن طفيل في جوانب الفلسفة الإسلامية. هذا البحث عبارة عن بحث مراجعة أدبية مع التركيز على الوصف النوعي الذي يحاول تحليل الأفكار القائمة على الكتب أو غيرها من الأعمال البحثية التي تناقش بشكل جوهري أفكار المفكر الإسلامي ، وهو ابن طفيل. تؤكد نتائج الدراسة أن سياق فكر ابن طفيل في مجال الفلسفة الإسلامية تأثر بسياق حقائق حياة ابن طفيل ، أي التطور الهائل في العلم. الكلمات المفتاحية: الفلسفة الإسلامية ، ابن طفيل ، الفكر الإسلامي Abstrak Pemikiran filsafat Islam sebenarnya merupakan kajian yang membahas tentang hakikat dan substansi pemikir. Sebagai seorang pemikir Islam, tentunya berbagai pemikiran filosofis Islam berkaitan dengan ajaran Islam. Hal ini bisa dimaklumi karena Islam seolah menjadi “mata air” di tengah gurun pasir yang kering. Penelitian ini bertujuan untuk menggali pemikiran Ibn Thufail dalam aspek filsafat Islam. Penelitian ini merupakan penelitian tinjauan pustaka dengan mengutamakan kualitatif-deskriptif yang mencoba menganalisis pemikiran berdasarkan buku atau karya penelitian lain yang secara substantif membahas pemikiran seorang pemikir Islam, yaitu Ibn Thufail. Hasil kajian menegaskan bahwa konteks pemikiran Ibn Thufail dalam bidang filsafat Islam dipengaruhi oleh konteks realitas zaman Ibn Thufail hidup, yaitu perkembangan ilmu pengetahuan yang masif. Kata Kunci: Filsafat Islam; Ibn Thufail; Pemikiran Islam